Domestic child abuse and family realm in Albania - Dini, Elona; Mersini, Kujtim (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper brings new insights and further examines the data obtained from the National Survey of Domestic Violence, which is the most comprehensive source on the prevalence of violence against children in Albania.The aim here is not to duplicate or overlap with the results of the survey but to enshrine subtle elements that characterize the violence against children. The analyses are focused to critically examine the frequency and characteristics of physical violence against children. This includes the calculation of many comparisons between the occurrence of violence and predisposing factors. From the statistical analysis results, it can be seen, that the number of respondents who nominated their respective mothers as offenders represent 70% of the total valid sample followed by their fathers and brothers/sisters with 46% and 38% respectively. It appears that the most frequent and sadly culturally accepted method of physical violence against children is slapping and knuckle beating which resulted in 89% of cases followed by hair tear and pushes by 60%, meanwhile other more extreme forms of violence occur to a lower rate ranging from 0.6% up to 20%. Interestingly the violence against children is predominantly high in Elbasan and Gjirokastra regions with an outstanding prevalence of 91% and 88% respectively. These scientific facts replace the old misconceptions that the domestic violence is more widespread in northern areas of Albania. The research findings reported here are critical to inform our efforts to protect children from children’s exposure to violence.